Radio production making a radio commercial - Pratt, Robert, director (North Ryde, NSW. : Australian Film Television & Radio School, 1986)
The video shows how to go about making a radio advertisement.
Copy available in DVD format.
Keywords: Radio advertising; Broadcast advertising; Advertising